A máquina, tração do progresso: mémorias da ferrovia no Oeste de Minas entre o sertão e civilização 1880-1930 - Pablo Luiz de Oliveira Lima (2003)
This Social-cultural History dissertation aims to approach the railways place west Minas Gerais memory and History. It analysis the transformation process of frontier-lands (sertão) into western civilization spaces, between 1880 and 1930, in travellers, politicians and entrepreneurs literature. The diagnosis of brazillian backwardness, justifying progress, is questioned. In the official political speech of Minas Gerais province and state administrators, relations between the railway and modern nation building, linked with regional development, are discussed. The study focuses on the planning and working processes of the West Minas Gerais (EFOM) and Goiás (EFG) railroads. Through representations found in west Minas Gerais regional press, photographic images and oral interviews, the place of labor in the memories made both by the companies and the wokers is analysed.